PEMANFAATAN BUKU TEKS OLEH GURU EKONOMI SMA NEGERI SE-KABUPATEN OGAN ILIR - Yunita Leni Utari; Deskoni Deskoni; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2017)
Abstract: This study discusses the use of textbooks by economics teacher based on curriculum 2013 high schools in Ogan Ilir. The formulation of the research problem are